2010
DOI: 10.1111/j.1365-2745.2010.01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Solidago gigantea in contrasting experimental plant communities: effects on soil microbes, nutrients and plant–soil feedbacks

Abstract: Summary1. Plant-soil feedbacks can influence the success of non-native plant invasions. We investigated if these feedbacks and the underlying invasion effects on soil microbes and nutrients depend on the species composition of the invaded vegetation, and whether these effects are related to differences in the invasibility of native plant communities. 2. We carried out a mesocosm experiment simulating the invasion of Solidago gigantea into three wetland plant communities (Molinion, Magnocaricion and Filipenduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 68 publications
6
58
0
Order By: Relevance
“…Both plant species increased mycorrhizal frequency but decreased species richness of AMF (Zubek et al unpublished). Our results agree with those of Scharfy et al (2009Scharfy et al ( , 2010 and Quist et al (2014) who found that S. gigantea invasion had no influence or decreased soil respiration, bacterial biomass, or phosphomonoesterase activity but increased fungal biomass and/or fungal:bacterial ratio. S. gigantea litter may support fungal rather than bacterial growth as it has lower tissue concentrations of most nutrients and higher C:N ratio than adjacent native vegetation Thorn and Lynch 2007;Dassonville et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Both plant species increased mycorrhizal frequency but decreased species richness of AMF (Zubek et al unpublished). Our results agree with those of Scharfy et al (2009Scharfy et al ( , 2010 and Quist et al (2014) who found that S. gigantea invasion had no influence or decreased soil respiration, bacterial biomass, or phosphomonoesterase activity but increased fungal biomass and/or fungal:bacterial ratio. S. gigantea litter may support fungal rather than bacterial growth as it has lower tissue concentrations of most nutrients and higher C:N ratio than adjacent native vegetation Thorn and Lynch 2007;Dassonville et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, such differences in tissue nutrient concentrations were not found by other authors (Stefanowicz et al unpublished). High fungal biomass detected in this study may suggest that S. gigantea stimulates fungal pathogens in its introduced range (Scharfy et al 2010), as shown previously for other invasive species (Nijjer et al 2007;Mangla et al 2008). For example, Mangla et al (2008) found that Chromolaena odorata, a destructive tropical invasive weed, accumulated high concentrations of the generalist soil-borne fungi, Fusarium semitectum, thereby creating a negative feedback to native plant species.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To date, only few experimental studies have tested the impact of I. glandulifera, R. japonica, R. laciniata, or S. gigantea on soil (Scharfy et al 2010(Scharfy et al , 2011Bardon et al 2014Bardon et al , 2016. Scharfy et al (2010) performed a mesocosm experiment simulating the invasion of a single species-S. gigantea into three wetland plant communities and found no invasion effect on N and P availability in soil.…”
Section: Introductionmentioning
confidence: 99%